2021
DOI: 10.1007/s10903-021-01180-0
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Mental Health Among Syrian Refugee Children in Jordan

Abstract: Refugee populations are at high risk of experiencing trauma and developing negative mental health outcomes. The resilience of Syrian refugee children is not well established as far as modifying the association between trauma and mental illness. A total of 339 Syrian refugee children aged 10 to 17 were surveyed to assess resilience, depression and history of trauma. All children reported exposure to at least one traumatic event, 48.6% reported exposure to highly salient traumatic events such as being held hosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…International Journal of Women's Health 2022:14 1260 events. 5,24,35,[46][47][48][49] The loss of the head of household in conservative societies exposes women to plenty of new life stressors that are not common. Also, experiencing conflict-related traumatic events by the majority of participants is another possible reason for the high levels of distressing emotional symptoms among the study participants, including a refuge journey, personal injury threats, personal death threats, losing one's home, and having a family member(s) death, missing, or injury.…”
Section: Dovepressmentioning
confidence: 99%
“…International Journal of Women's Health 2022:14 1260 events. 5,24,35,[46][47][48][49] The loss of the head of household in conservative societies exposes women to plenty of new life stressors that are not common. Also, experiencing conflict-related traumatic events by the majority of participants is another possible reason for the high levels of distressing emotional symptoms among the study participants, including a refuge journey, personal injury threats, personal death threats, losing one's home, and having a family member(s) death, missing, or injury.…”
Section: Dovepressmentioning
confidence: 99%
“…Resilience is de ned as a multisystemic dynamic process of successful adaption or recovery in the context of risk or a threat(38), that is, the ability to bounce back to regain functional equilibrium in a state of health in response to stressful events and positive adaption even in face of signi cant threat and/or adversity (39). A study in 339 adolescents reported that higher levels of resilience were related to fewer symptoms of depression (40). A cross-sectional survey of Ghanaian adolescents aged 13-17 years showed there was a negative correlation between resilience and anxiety (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have examined the mediating effect of resilience on internalizing and externalizing problems, and various other factors. For example, previous research showed resilience had a mediating effect between stressful life events and anxiety [ 49 ], between sleep and behavioral and emotional problems [ 50 ], and between trauma, and depression [ 51 ]. Previous studies reported beneficial outcomes facilitated by resilience on enhancing positive behaviors, healthy relationships with peers, and school-related outcomes in school children [ 35 ].…”
Section: Introductionmentioning
confidence: 99%